Synthesis and characterization of novel alpha- or beta-tetra[6,7-dihexyloxy-3-(4-oxyphenyl)coumarin]-substituted metal-free and metallo phthalocyanines - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
The synthesis of novel phthalonitriles substituted at 3- or 4-position with 6,7-dihexyloxy-3-(4-oxyphenyl)coumarin were performed. The metal-free and metallo phthalocyanines (MPcs) (M = Zn, Co, Cu) were prepared by cyclotetramerization of 6,7-dihexyloxy-3-[p-(2',3'-dicyanophenoxy)phenyl]coumarin or 6,7-dihexyloxy-3-[p-(3'.4'-dicyanophenoxy)phenyl]coumarin. The newly prepared compounds, phthalonitriles and Pcs, have been characterized by elemental analysis, H-1 NMR, C-13 NMR, MALDI-TOF, IR, UV-Vis and fluorescence spectral data. The electronic spectra exhibit bands of coumarin identity along with characteristic Q and B bands of the Pc core. The IR-spectra of all Pcs showed three characteristic intense bands at 1709-1700 cm(-1) for lactone carbonyl, two bands at 1489-1604 cm(-1) for conjugated olefinic system. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Coumarin; Fluorescence; Aggregation; Zinc; Cobalt; Copper; EXTRACTION